2018
DOI: 10.3389/fmicb.2018.00077
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriome from Pinus arizonica and P. durangensis: Diversity, Comparison of Assemblages, and Overlapping Degree with the Gut Bacterial Community of a Bark Beetle That Kills Pines

Abstract: Symbioses between plants and microorganims have been fundamental in the evolution of both groups. The endophytic bacteria associated with conifers have been poorly studied in terms of diversity, ecology, and function. Coniferous trees of the genera Larix, Pseudotsugae, Picea and mainly Pinus, are hosts of many insects, including bark beetles and especially the Dendroctonus species. These insects colonize and kill these trees during their life cycle. Several bacteria detected in the gut and cuticle of these ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…The sequencing proceeds through a cycle of washing and flooding fragments with known nucleotides in sequential order. As nucleotides incorporate into the growing DNA strand, they are digitally recorded as a sequence [22][23][24]. Three basic platforms can be distinguished in NGS: Roche 454-pyrosequencing, Ion Torrent, and Illumina sequencing.…”
Section: Next Generation Sequencing Platforms As An Effective Tool Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The sequencing proceeds through a cycle of washing and flooding fragments with known nucleotides in sequential order. As nucleotides incorporate into the growing DNA strand, they are digitally recorded as a sequence [22][23][24]. Three basic platforms can be distinguished in NGS: Roche 454-pyrosequencing, Ion Torrent, and Illumina sequencing.…”
Section: Next Generation Sequencing Platforms As An Effective Tool Inmentioning
confidence: 99%
“…A list of the most recent metagenomic studies [11][12][13][14][15][16][17]23,24,[32][33][34][35][36][37][38][39][40] has been prepared to summarize endophyte strains that can be potentially employed for specific plants and properties that have been enhanced (Table 1). It was demonstrated that plant growth promoting (PGP) abilities and biological nitrogen fixation, followed by the production of secondary metabolites and bioactive compounds, synthesis of fungicides and bactericides, and protection against environmental stresses are the most important benefits that are provided to plants by endophytes (Table 1).…”
Section: Next Generation Sequencing Platforms As An Effective Tool Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet is a very important factor in shaping the gut microbiota of insects [31,44]. Plant endophytic bacteria might exist in plant-feeding insects and help regulate insect development [20,45]. In our study, PTM midgut microbes and potato endophytic communities showed significant differences.…”
Section: Discussionmentioning
confidence: 56%
“…Some endophytic bacteria from plant tissues might be the same as those present in the insect gut [20], and can establish microbial communities in plant-feeding insect guts after transference from a plant [21]. Some studies have shown that many bacterial endophytes colonize the inner tissues of potato organs [22][23][24] and can promote growth and enhanced resistance of potato plants to pathogenic bacteria and fungi [25][26][27].…”
Section: Introductionmentioning
confidence: 99%